DAKWAH DAN EPISTIMOLOGI DALAM KHAZANAH FILSAFAT ISLAM - Riyadi, Agus (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2012)
Da?wah (Islam) should not only at the conception but trying to get a more in-depth knowledge and connect with the target object (pure science and applied science). Dakwah without understanding the philosophical-epistemological foundation will lead to understanding of the Da?wah (Islamic) becomes shallow and oven cause/make its adherents are stuct into the formalism and narrow fanaticism, on the contrary, the understanding of Dakwah which at based on philoshopical?epistelomogical will bring Dakwah at understanding essentially and in depth, so avoiding from conflicts caused by the many isms or others.There are at least three forms that can be used as a reference deals with the means of scientific development of Dakwah, which deals with the means Bayani, deals with the means Irfani and deals with the means Burhani. Burhani, the patterns of thought derived from the texts (Nash) then Irfani the patterns of thought proceed from zauq, qalb, , or intuition, while Burhani rooted in intellectual activities to establish the truth of a proposition by the deductive method, i.e by linking to each other proposition that are axiomatic. The three forms of epistemology above, will determine the dynamics and characteristic of the science of Dakwah.